Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1111/j.1365-3156.2004.01299.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori antigens in the faeces of asymptomatic children in the Buea and Limbe health districts of Cameroon: a pilot study

Abstract: Summaryobjective To determine the prevalence and identify intra-familial risk factors associated with Helicobacter pylori infection in a paediatric population. conclusions This study highlights the continuing importance of age, sex and socioeconomic status in the acquisition of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
77
7
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 18 publications
(23 reference statements)
13
77
7
4
Order By: Relevance
“…This supports results obtained by meta-analysis of 10 studies conducted over the last 20 years which found no sex difference regarding prevalence of H. pylori among children (de Martel and Parsonnet, 2006). Higher prevalence in males or in females was reported in different other studies (Klein et al, 1994;Ndip et al, 2004;Dube et al, 2009). …”
Section: Discussionsupporting
confidence: 89%
“…This supports results obtained by meta-analysis of 10 studies conducted over the last 20 years which found no sex difference regarding prevalence of H. pylori among children (de Martel and Parsonnet, 2006). Higher prevalence in males or in females was reported in different other studies (Klein et al, 1994;Ndip et al, 2004;Dube et al, 2009). …”
Section: Discussionsupporting
confidence: 89%
“…The distribution of H. pylori as influenced by sources of water used in our study did not show any significant association between the sources of water used and H. pylori infection in patients ( [13]. Several other studies had highlighted the presence of the microorganism or their DNA in water [7,[14][15][16].…”
Section: Discussioncontrasting
confidence: 47%
“…Sharing of spoons, cups, premastication for young children, sharing water for bathing and washing hands and limited sanitary facilities have also been shown to be associated with increased prevalence of the organism [13,3].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies supported the observation that early childhood is the main period of acquisition of H. pylori infection in high prevalence population. One study conducted in Cameroon, using an enzyme-linked immunosorbent assay, the H. pylori stool antigen (HpSA) test reported a similar prevalence of 37.5% in children younger than 3 years [17]. Ceylan et al [18] reported that the prevalence of H. pylori ranged from 4.62% in children less than 5 years old to 70.76% among group aged 11-15 years, in Turkey.…”
Section: Discussionmentioning
confidence: 99%